MAJELIS TAKLIM DAN PERANANNYA DALAM PENINGKATAN DAKWAH DI KECAMATAN WARA SELATAN KOTA PALOPO - Ramlah M (Palita: Journal of Social Religion Research, 2017)
Religious life in the city of Palopo in recent times again looks lively. It is an indication of a change in social life, the culture of economic politics in society. One form of the development of religious life, especially in the formation of the ummah is the growing splendor majelis taklim institution which is one of the nonformal educational institutions that have the function and role in the guidance of the ummah, as a place of spiritual education and as a place of syiar Islam and silaturrahmi between ulama, umara (government ) with the people. This research will examine the important role played by majelis taklim institution in increasing the activity of da'wah and religious development in South Wara Subdistrict of Palopo City.